A post-crisis slump in Europe: A business cycle accounting analysis - Florian Gerth; Keisuke Otsu (University of Kent, School of Economics, 2016)
This paper analyses the Post-crisis slump in 29 European economies during the 2008Q1 - 2014Q4 period using the Business Cycle Accounting (BCA) method á la Chari, Kehoe and McGrattan (2007). We find that the deterioration in the efficiency wedge is the most important driver of the European Great Recession and that this adverse shock persists throughout our sample. Moreover, we find that the growth rate of non-performing loans are negatively associated with the decline in efficiency wedges. These findings support the emerging literature on resource misallocation triggered by financial crises
Keywords: E13; E32; 330; Great Recession in Europe; Business Cycle Accounting